Diagnostic and Prognostic Value of Serum Lactate Dehydrogenase and Amylase in Severe Acute Pancreatitis: A Clinical Biochemistry–Based Evaluation: Serum LDH and AMY as Biochemical Predictors of SAP - Zheng, Jie; Wang, Jin; Zhou, Yinong; Yu, Tingting (Journal of Medical Biochemistry, 2026)
Summary Background: Severe acute pancreatitis (SAP) is characterized by extensive acinar-cell injury, metabolic dysregulation, and systemic inflammatory activation. Reliable biochemical markers for early risk stratification remain limited. Lactate dehydrogenase (LDH) and amylase (AMY), routinely measured enzymes reflecting cellular damage and pancreatic exocrine dysfunction, may provide prognostic value. To evaluate the diagnostic performance of serum LDH and AMY in identifying SAP and predicting short-term outcomes. Methods: This retrospective study included 200 patients with acute pancreatitis. Serum LDH and AMY were measured on admission using standardized clinical chemistry assays with internal quality control. Patients were categorized as MAP, MSAP, or SAP, and SAP cases were further stratified into good and poor 2-week prognosis groups. Logistic regression and ROC analyses were used to determine the predictive value of LDH and AMY. Results: LDH and AMY levels increased significantly with disease severity (P<0.05). Both biomarkers were independent predictors of SAP (LDH OR=1.644; AMY OR=1.670) and poor prognosis (LDH OR=1.684; AMY OR=1.730). Combined LDH+AMY demonstrated superior predictive accuracy for SAP (AUC=0.854) and short-term poor prognosis (AUC=0.884), outperforming individual markers. Conclusions: Serum LDH and AMY are clinically valuable biochemical indicators for early identification of SAP and prediction of short-term outcomes. Their combined use significantly enhances diagnostic accuracy, supporting their integration into early biochemical risk assessment models.